Evaluation of Educational Supply Chain Management for Secondary School Supervisory Performance in Bengkulu City - Iswadi Idris (International Journal of Supply Chain Management, 2020)
Abstract-The purpose of this paper is to implement the philosophy of supply chain management in the current higher education environment so as to suggest innovative management ideas in higher education management. The objective of study is to find out the performance of senior high school supervisors in Bengkulu City regency Bengkulu Province that consists of: (1) composing supervisory planning, (2) carrying out the supervisory planning, (3) evaluating the implementation of the supervisory planning, and (4) guiding and training of professional teachers and school principals based on the supply chain management. The research was conducted in regencies and cities in central Bengkulu regency Bengkulu province. The subject of research is senior high school supervisor in Bengkulu City Bengkulu province (29 persons). The method of research is mixed method. The research design used Provus is Descrepancy Evaluation Models (DEM). The data were colected by using observation, interview, questionnaire and documents. The results of research shows that: (1) the performance of supervisors in composing plannings is very good category, (2) the performance of supervisors in carrying out sepervisory planning is good category, (3) the performance of supervisors in evalauating the product of implementation of the supervisory planning is fair category, and (4) the performance of supervisors in guiding and training of professional teachers or school principals in Bengkulu City Bengkulu province is poor category.